New Formulation of Trimethoprim Injectable Solution for Veterinary Use: Arooba M.S. Ibrahim and Duraid A. H. Abbas - Ibrahim, Arooba M.S. (The Iraqi Journal of Veterinary Medicine, 2012)
The aim of this study was prepared new formulation of trimethoprim injectablesolution in the Physiology and pharmacology department /College ofVeterinaryMedicine, University of Baghdad.Trimethoprim injection formulation is antibacterial andused against a number of bacteria, protozoa and Rickettsia. Data was collected about thematerials used in the preparation of the formula from the well-known pharmacopeia,including the specification, physical and chemical properties of active ingredient, theadditive and preservative that must be used. Three pilot formulae were prepared fromanalar chemical ingredient from which one formula was chosen and tested to approve itsquantitative and qualitative specification. Quantitative evaluation, stability of theformula was also tested under different storage environmental condition of low and hightemperature at different periods through and one year and through the questionnaire field.Questionnaire proved the product, stability and therapeutic efficiency. The compositionobtained a certificate of acceptance from the Veterinary State Company and VeterinaryDrug Research and production Centre as new preparation Formula of TrimethoprimInjectable Solution for Veterinary use.